1990
DOI: 10.3109/10799899009064670
|View full text |Cite
|
Sign up to set email alerts
|

Multiple [3H]-Oxytocin Binding Sites in Rat Myometrial Plasma Membranes

Abstract: The affinity spectrum method has been used to analyse binding isotherms for [3H]-oxytocin to rat myometrial plasma membranes. Three populations of binding sites with dissociation constants (Kd) of 0.6-1.5 x 10(-9), 0.4-1.0 x 10(-7) and 7 x 10(-6) mol/l were identified and their existence verified by cluster analysis based on similarities between Kd, binding capacity and Hill coefficient. When experimental values were compared to theoretical curves constructed using the estimated binding parameters, good fits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
3
11
1
Order By: Relevance
“…The present study revealed a single population of high-affinity binding sites using [' HJoxytocin concen¬ trations of up to 20 nmol/1; however, in addition to a high-affinity site, two additional lower affinity oxytocinbinding sites have been demonstrated in cultured sheep myometrial cells (Pliska et al 1986) and rat myometrial plasma membranes (Crankshaw et al 1990), which would not have been detected here. It has been argued that these lower affinity sites are of physiological significance to the actions of oxytocin (Crankshaw et al 1990, Pliska 1991.…”
Section: Discussioncontrasting
confidence: 52%
“…The present study revealed a single population of high-affinity binding sites using [' HJoxytocin concen¬ trations of up to 20 nmol/1; however, in addition to a high-affinity site, two additional lower affinity oxytocinbinding sites have been demonstrated in cultured sheep myometrial cells (Pliska et al 1986) and rat myometrial plasma membranes (Crankshaw et al 1990), which would not have been detected here. It has been argued that these lower affinity sites are of physiological significance to the actions of oxytocin (Crankshaw et al 1990, Pliska 1991.…”
Section: Discussioncontrasting
confidence: 52%
“…Only one class of binding sites was detected (K d ϭ 6.3 ϫ 10 Ϫ9 M), which is in keeping with results obtained in saturation and homologous competition studies in pregnant women [11,14] but contrasts with similar studies in rats, sheep and cattle [19,20]. In these studies at least two saturable binding sites were found (approx.…”
Section: Discussionsupporting
confidence: 80%
“…In these studies at least two saturable binding sites were found (approx. K d ϭ 5 ϫ 10 Ϫ9 M and 4 ϫ 10 Ϫ7 M) [19,20]. This raised the question of the identity of the oxytocin receptor [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few data are available as regards OT receptor subtypes and mainly concern the uterus. Thus, three OT receptor subtypes according to their affinity for OT have been reported on myometrial plasma membranes in the rat (Crankshaw et al 1990). In the same species, the effects of OT on the myometrium and the endometrium are mediated by two OT receptor subtypes having distinct pharmacological characteristics (Chan et al 1993).…”
Section: Discussionmentioning
confidence: 99%